Participation and its diminishing factors in aquatic lessons - Ruokanen, Anniina (2025)
Aquatic education is a key component of physical education, fostering life-saving skills and well-being. The Finnish curriculum mandate annual aquatic teaching. However, despite these guidelines swimming proficiency among sixth graders has declined and student participation is perceived to be low. This study examines students’ participation levels, reasons for absence and teachers’ strategies to support participation in aquatic education in lower and upper secondary schools.